Microfinanzas: diagnóstico del sector de la micro y pequeña empresa y su tecnología crediticia - Toledo Concha, Emerson (2009)
This research work shows how the financing for micro and small businesses in Peru has increased and has greatlyexpanded in the last few years, not only in institutions specialized in this field, focused their efforts in giving financialservices to businesspeople of micro and medium-sized business, but most of the so-called traditional banks havefocused their attention to this emerging sector using the know-how of microfinance lending technology, banking seekto work with people of low income sectors, that were not subject for credit opportunities to develop their business andas a consequence not able to improve their quality of life .Throughout this investigation, we make a diagnosis of macro and micro environment of the microfinance field, itsdevelopment and expectations for a strong presence in the Peruvian financial market. We consider the development oflending technology, where the analysis of the ability and willingness to pay are the fundamental basis for the evaluationof credits in specialized companies in this sector.